Mounting challenges, declining resource and rising expectations in the Asia and Pacific Region - Nakamura, Akira (Asian Review of Public Administration, 2011)
The principal agenda of the EROPA 2011 conference was Challenges, Opportunities and Innovation in Public Administration in the Next Decade, and there were three sub-themes: 1) fiscal retrenchment: challenges opportunities and innovation public administration: 2) the role of the state in managing new challenges, opportunities and innovation; and 3) innovations in public service delivery. The major agendas and the three sub-themes are all highly germane to current conditions in the Asia and the Pacific region. In this part of the world, challenges to government abound. Some countries are facing political issues, while others must attend to economic problems. Against that backdrops, this article first describes a number of challenges which various governments in Asia are currently confronted with. It then delineates opportunities and innovations which may help alleviate impediments to good government action in the region.